2020
DOI: 10.1002/jsfa.10312
|View full text |Cite
|
Sign up to set email alerts
|

Selection of tomato landraces with high fruit yield and nutritional quality under elevated temperatures

Abstract: BACKGROUND Global warming and extreme or adverse events induced by climatic fluctuations are an important threat for plants growth and agricultural production. Adaptability to environmental changes prevalently derives from a large set of genetic traits affecting physiological and agronomic parameters. Therefore, the identification of genotypes that are good yield performer at high temperatures is becoming increasingly necessary for future breeding programs. Here, we analyzed the performances of different tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 42 publications
(100 reference statements)
2
42
0
Order By: Relevance
“…and Wang and Zheng 5 observed a significant increase in the antioxidant capacity of strawberries due to HS. A thermal shock can activate different biochemical mechanisms, such as the synthesis of pigments and secondary metabolites (antioxidant compounds, osmoprotectants and heat‐shock proteins) 6,7 . The production of fruits rich in antioxidant compounds is of great interest, with regard to the prevention of diseases as well as cancer or cardiovascular pathologies in humans 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Wang and Zheng 5 observed a significant increase in the antioxidant capacity of strawberries due to HS. A thermal shock can activate different biochemical mechanisms, such as the synthesis of pigments and secondary metabolites (antioxidant compounds, osmoprotectants and heat‐shock proteins) 6,7 . The production of fruits rich in antioxidant compounds is of great interest, with regard to the prevention of diseases as well as cancer or cardiovascular pathologies in humans 8 …”
Section: Introductionmentioning
confidence: 99%
“…A thermal shock can activate different biochemical mechanisms, such as the synthesis of pigments and secondary metabolites (antioxidant compounds, osmoprotectants and heat-shock proteins). 6,7 The production of fruits rich in antioxidant compounds is of great interest, with regard to the prevention of diseases as well as cancer or cardiovascular pathologies in humans. 8 Polyamines (PAs) are low-molecular-weight aliphatic amine bases and include putrescine (Put), spermine and spermidine, which have strong biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…A higher concentration of this carotenoid was found in green fruits of the two landraces when compared to 'Moneymaker' , whereas in ripe fruits, only the landrace Negro Yeste had a higher amount, even more than double. Also in comparison with the commercial variety 'Moneymaker' , three tomato landraces, two from Italy and one from Guatemala, showed a significantly higher β-carotene content [29]. In other study carried out in melon (Cucumis melo L.), landraces of different origins exhibited the highest levels of β-cryptoxanthin and β-carotene compared with commercial melons [30].…”
Section: Vitamin Amentioning
confidence: 74%
“…In addition, CIDA-62 fruits showed the highest antioxidant activity, whereas the lowest was observed in the commercial variety [42]. Other authors also reported 10 indeterminate tomato landraces that exhibited significantly higher AA contents than the commercial variety 'Moneymaker' [29]. In analyses of the AA content in accessions of garlic (Allium sativum L.) from Plugia region (Italy), the six landraces evaluated had a higher content than the commercial cultivar used as reference [43].…”
Section: Vitamin Cmentioning
confidence: 88%
See 1 more Smart Citation